Soft-bottom communities in Balsfjord. Stable over time of under change? - Henriksen, Nina Elisabeth (UiT Norges arktiske universitet, 2015)
The soft-bottom macrofauna (>1 mm) was investigated at three different locations in Balsfjord; Andersdal, Svartnes and Tennes. The Svartnes data was then merged with Eivind Ougs long-term series from 1977-1994. The data showed that there were large variation between the three different stations in number of taxa and individuals found. A total of 59 taxa and 1514 (0.7 m2) individuals were found. The polychaeta Maldane sarsi and Galathowenia oculata were the dominate taxa at all three stations in number of individuals but the echinoderm Ctenodiscus cripatus dominated in biomass at Andersdal and Tennes. Andersdal was found to have the most number of taxa and individuals. Svartnes was the most divers with Shannon-Wiener index of 2.54 followed by Tennes with 1.99 and Andersdal with 1.69. The long-term study showed that species assemblage had changed little, but that the number of individuals had decreased from 1994 to 2013. Tubificoides cruspisetosus that was found in large numbers in 1994, was found in only one of the grab samples at Svartnes, represented by only one individual. Long-term monitoring in Balsfjord is now more important than ever since 3 small red king crab Paralithodes camtschaticus was captured in October 2014 at Tennes, especially considering the potential effect this invasive species has on the ecosystem.